“DAMPAK TANGGUNG JAWAB SOSIAL PERUSAHAAN (CSR) DAN TATA KELOLA PERUSAHAAN (GCG) TERHADAP KINERJA KEUANGAN MENGGUNAKAN MANAJEMEN LABA SEBAGAI VARIABEL MEDIASI“ (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2019” - Irfan Herdiansyah; Imam Ghozali (Diponegoro Journal of Accounting, 2021)
This scientific paper aims to examine the Impact of Corporate Social Responsibility (CSR) and Corporate Governance (GCG) on Financial Performance Using Profit Management as a Mediation Variable (Empirical Study of Manufacturing Companies Listed on the Indonesia Stock Exchange 2018-2019). The background of this research is because financial performance is one of the indicators that can be used to measure whether a company is getting the expected profit and to fulfill its obligations to investors in order to achieve company goals. Two factors that affect the company's financial performance are corporate social responsibility (CSR) and corporate governance mechanisms (GCG). Earnings management which is used as a mediating variable in this study was chosen because it can describe the asymmetry of information about the state of the company between the owner (principal) and management (agent) where management does not provide true information about the condition of the company. This study shows that corporate social responsibility (CSR) and corporate governance (GCG) have a positive influence on financial performance, corporate social responsibility (CSR) has a positive effect on earnings management, and earnings management has a negative effect on management. profit.